Glucocorticoids are induced while dihydrotestosterone levels are suppressed in 5‐alpha reductase inhibitor treated human benign prostate hyperplasia patients. Issue 14 (12th July 2022) - Jin, Renjie; Forbes, Connor; Miller, Nicole L.; Strand, Douglas; Case, Thomas; Cates, Justin M.; Kim, Hye‐Young H.; Wages, Phillip; Porter, Ned A.; Mantione, Krystin M.; Burke, Sarah; Mohler, James L.; et al.
Abstract: Background: The development of benign prostatic hyperplasia (BPH) and medication‐refractory lower urinary tract symptoms (LUTS) remain poorly understood. This study attempted to characterize the pathways associated with failure of medical therapy for BPH/LUTS. Methods: Transitional zone tissue levels of cholesterol and steroids were measured in patients who failed medical therapy for BPH/LUTS and controls. Prostatic gene expression was measured using qPCR and BPH cells were used in organoid culture to study prostatic branching. Results: BPH patients on 5‐α‐reductase inhibitor (5ARI) showed low levels of tissue dihydrotestosterone (DHT), increased levels of steroid 5‐α‐reductase type II (SRD5A2), and diminished levels of androgen receptor (AR) target genes, prostate‐specific antigen (PSA), and transmembrane serine protease 2 (TMPRSS2). 5ARI raised prostatic tissue levels of glucocorticoids (GC), whereas alpha‐adrenergic receptor antagonists (α‐blockers) did not. Nuclear localization of GR in prostatic epithelium and stroma appeared in all patient samples. Treatment of four BPH organoid cell lines with dexamethasone, a synthetic GC, resulted in budding and branching. Conclusions: After failure of medical therapy for BPH/LUTS, 5ARI therapy continued to inhibit androgenesis but a 5ARI‐induced pathway increased tissue levels of GC not seen in patients on α‐blockers. GC stimulation of organoids indicated that the GC receptors are a trigger for controlling growth of prostate glands. A 5ARI‐induced pathway revealed GC activation can serve as a master regulator of prostatic branching and growth.